Risk Communication for the Future Towards Smart Risk Governance and Safety Management - Bourrier, Mathilde; Bieder, Corinne (SpringerBriefs in Safety Management,, 2018)
The conventional approach to risk communication, based on a centralized and controlled model, has led to blatant failures in the management of recent safety related events. In parallel, several cases have proved that actors not thought of as risk governance or safety management contributors may play a positive role regarding safety. Building on these two observations and bridging the gap between risk communication and safety practices leads to a new, more societal perspective on risk communication, that allows for smart risk governance and safety management. This book is Open Access under a CC-BY licence.    .